Residual Activity of Metarhizium anisopliae or Plant Extracts on Laying Hens for Menacanthus stramineus Lice Control by Dipping - Pablo, E.S.; Sandoval, A.L.M.; Fernandez, M.R.; Morales, E.; Prado, O.; Tellez, G.; Quintero, M.T.M. (International Journal of Poultry Science, 2009)
In the present study, eighty-four Hy-Line W36 laying hens in two experiments were distributed in 7 treatments with 3 replicates of four hens each. Each treatment, hens received 3 dipping/2 min every 48 h. Residual activity was done by counting lice one month after dipping. Treated hens with no live lice were reinfested with 20 lice and repeated during three months. In experiment one, aqueous suspensions of three plant extracts were tested as dips for control of MS lice: a) Neem (Azadirachta indica) 500 ppm; b) Ruda (Ruta graveolens) 11,700 ppm; or c) Solanacea (Ardisia solanacea) 50,000 ppm; d) Negative Control (water). After the first dipping, a significant difference (p<0.05) in the number of dead lice were observed in the hens that received Neem (84.1%) or Solanacea (98.1%), however, after the second and third dipping, all treated groups showed a significant increase in the number of dead lice compared with the control. Average after the 3 dips was: Neem (93.6%); Ruda (85.2%); Solanacea (98.2%); Control (49.1%). One month later, all 3 treated groups had 0 lice compared with 38 lice in the control group. Counts of live lice at two months after first reinfestation were: Neem (0); Ruda (1); Solanacea (43); Control (51). Counts of live lice at three months after second reinfestation were: Neem (0); Ruda (15); Solanacea (NA); Control (60). In experiment two, 3 aqueous suspensions were tested: group 1) Ruda tincture 50,000 ppm; group 2) Coumaphos 1,000 ppm; or group 3) M. anisopliae 50,000 ppm. After the first dipping, a significant difference in the number of dead lice were observed in the hens that received Coumaphos (100 %), however, no significant differences were observed between treatments after the second and third dipping Counts of live lice one month later were: group 1 (2 lice); group 2 (0 lice); group 3 (38 lice). Counts of live lice at two months after first reinfestation were: group 1 (13) and group 2 (16). The results of the present study suggest that some alternative bio-control methods for lice in laying hens are effective.